Demonstrasi Minoritas Muslim Dalam Berdakwah di Negeri Non-Muslim - Abidin, Idrus; Majid, Zamaksyari Abdul; Nurhaidah, Siti Nuri; Akbar, Muhammad Yudi Ali; Hayatuddin, Hayatuddin; Evalinda, Evalinda; Hamid, Lallo (LP2M Universitas Islam Ahmad Dahlan, 2024)
This research analyzes how demonstrations are viewed by contemporary Muslim intellectuals. The research method is based on a qualitative approach with a literature study basis. Primary references use recent studies with a number of pros and cons that have occurred between the main supporters (Ikhwanul Muslimin) and those who strongly oppose it (Madkhaliyah). Secondary references use indirectly related research. The research findings show that there are 4 characteristics of Muslim-majority countries that need to be differentiated concerning the law of demonstrations: (1) Muslim-majority countries that adopt the principle of shura in their political system. Demonstrations are considered haram because of the principle of obedience to the government as long as it does not involve disobedience to God. (2) Muslim-majority countries that adopt the principle of democracy. Demonstrations are allowed, even recommended or obligatory, as long as they do not aim to annul the government. (3) Occupied Muslim-majority countries. Demonstrations in occupied Muslim-majority countries, such as intifada actions and the like, are considered obligatory. The obligation is not limited to demonstrations but extends to jihad, both defensive and offensive. (4) Demonstrations in non-Muslim countries are considered permissible as long as they do not create problems for the Muslim minority.